THE 1988 CONSTITUTION AS A CHARTER OF RESISTANCE IN THE FACE OF THE UNCONSTITUTIONAL STATE OF AFFAIRS IN THE PRISON SYSTEM: TRANSCONSTITUTIONALISM AS AN INSTRUMENT FOR THE ENFORCEMENT OF RIGHTS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
The 1988 Constitution consolidated its role as a Charter of Resistance and an instrument of democratic affirmation by enshrining human dignity, citizenship, and pluralism as foundational principles of the Democratic Rule of Law in Brazil. Despite its transformative potential, the Brazilian prison system remains marked by structural and persistent violations of fundamental rights, which challenge constitutional effectiveness. The recognition of the State of Unconstitutional Affairs (ECI) by the Federal Supreme Court (STF) in Allegation of Breach of Fundamental Precept (ADPF) nº 347 represents a constitutional response to the collapse of state structures and the systematic denial of rights within the prison system. In this context, the research is guided by the following question: how can the 1988 Constitution, understood as a Charter of Resistance, provide a legal and political foundation for strategies aimed at ensuring the rights of persons deprived of liberty? To address this question, the study examines the interaction between the State of Unconstitutional Affairs and Marcelo Neves’s theory of transconstitutionalism. This theory proposes the articulation among distinct legal orders to build shared solutions for constitutional problems involving human and fundamental rights, whose resolution requires a transnational normative dialogue. The analysis demonstrates that such articulation strengthens the normative force of the 1988 Constitution, broadens its dialogical capacity, and offers theoretical and institutional instruments to address structural violations in the Brazilian prison system. The research employs a deductive approach, monographic method, and qualitative analysis, based on specialized legal scholarship, judicial decisions, and official data.